Innate Immune Memory in Invertebrate Metazoans: A Critical Appraisal - Melillo, Daniela; Marino, Rita; Italiani, Paola; Boraschi, Diana (Frontiers in Immunology, 2018)
The ability of developing immunological memory, a characteristic feature of adaptive immunity, is clearly present also in innate immune responses. In fact, it is well known that plants and invertebrate metazoans, which only have an innate immune system, can mount a faster and more effective response upon re-exposure to a stimulus. Evidence of immune memory in invertebrates comes from studies in infection immunity, natural transplantation immunity, individual and transgenerational immune priming. These studies strongly suggest that environment and lifestyle take part in the development of immunological memory. However, in several instances the formal correlation between the phenomenon of immune memory and molecular and functional immune parameters is still missing. In this review, we have critically examined the cellular and humoral aspects of the invertebrate immune memory responses. In particular, we have restricted our analysis to studies that have addressed immune memory in the most restrictive meaning of the term, i.e., the response to a challenge of a quiescent immune system that has been primed in the past. These studies highlight the central role of an increase in the number of immune cells and of their epigenetic re-programming in the establishment of sensu stricto immune memory in invertebrates.